Limestones coated with photocatalytic TiO2 to enhance building surface with self-cleaning and depolluting abilities. (1st November 2017) - Calia, Angela; Lettieri, Mariateresa; Masieri, Maurizio; Pal, Sudipto; Licciulli, Antonio; Arima, Valentina
Abstract: Natural stones with self-cleaning and depolluting abilities are appealing to preserve building façades in polluted urban sites and simultaneously to provide air-purification. Coating with photocatalytic Titanium dioxide is promising at this purpose; nonetheless, stone coating issues need better insights to support large-scale applications. In this paper, photocatalytic surfaces of two limestones having different roughnessess and porosities, are investigated by comparing coatings obtained from either water and alcohol based colloidal suspensions of TiO2 nanoparticles, which were synthetized by sol gel and hydrothermal process and sprayed with different loads on the stone surface. A commercial water-based TiO2 sol was also used. The study aims to assess the role of the substrates, the nature of the titania dispersions and the TiO2 loads, in determining characteristics and properties of the photocatalytic stone surfaces, in order to obtain suited coatings for real applications on buildings. Colorimetry detected negligible colour changes on both stone surfaces due to the coatings. A photodegradation test of Rhodamine B recorded a high self-cleaning efficiency on the coated surfaces, irrespective of the stones, the alcohol and water based suspensions, and their TiO2 loads. Conversely, the efficiency in a NO x abatement test was dependent on the porosity and roughness of the stones. ESEM-EDS on the applied coatings and XRD on the TiO2 nanopowders identified critical issues in the coating morphology and presence of by-products relating to the preparation of the sols, which may have implications in the durability performances. The overall results showed that all the obtained coatings were able to deliver photocatalytic surface of both limestones, which have a potential to be implemented as eco-efficient materials on buildings. Nonetheless, higher air purification ability issued for the limestone with higher porosity and roughness and the experimental TiO2 water-based sol performed better than the alcoholic and commercial ones as regards the coating morphology and absence of by-products. Highlights: Water and alcohol based TiO2 sols synthetized by sol gel and hydrothermal process. Coating of limestones yielded photocatalytic surfaces with high self-cleaning ability. Abatement of NOx was dependent on the porosity and roughness of the limestones. Poor depolluting ability of the low porous limestone with the use of alcoholic sols. Critical issues in the film morphology and by- products of the preparation of sols.